Pengaruh Literasi Keuangan Syariah Dan Halal Lifestyle Terhadap Minat Menabung Gen Z Di Surabaya Pada Bank Syariah Dengan Selfcontrol Sebagai Variabel Moderasi - Muhammad Firdaus; Nurul Fatma Hasan (PT. Habe Cendekia Utama, 2026)
This study analyzes the influence of Sharia financial literacy and halal lifestyle on Generation Z’s interest in saving at Sharia banks in Surabaya, while examining the moderating role of self-control. Utilizing a quantitative approach, primary data were gathered through Likert-scale questionnaires distributed to 105 purposively selected Generation Z respondents in Surabaya. Data analysis was conducted using IBM SPSS version 25, employing multiple linear regression to evaluate direct effects and Moderated Regression Analysis (MRA) to test the moderating effects. The results indicate that Sharia financial literacy, halal lifestyle, and self-control individually exert a significant direct effect on Generation Z’s interest in saving at Sharia banks. However, self-control was not proven to moderate the influence of either Sharia financial literacy or halal lifestyle on their saving interest. These findings contribute academic and practical insights, particularly for Sharia banking institutions in formulating strategic policies to capture the Generation Z market by strengthening Sharia financial literacy programs and promoting the practical implementation of a halal lifestyle.